The Relative Contribution of Psychological Empowerment in Predicting Academic Self-Efficacy among Graduate Students at the College of Education at King Faisal University - Alismail, Abdulaziz Mohammed (Journal of Ecohumanism, 2024)
This study aimed to explore the role of psychological empowerment in predicting academic self-efficacy among graduate students at the College of Education, King Faisal University. It also investigated how these levels vary across different factors such as gender, department, and academic level. Additionally, the research aims to understand how psychological empowerment can predict academic self-efficacy among these students. Employing a descriptive, predictive, and correlational approach, the researcher utilized scales for psychological empowerment and academic self-efficacy to collect data from 268 graduate students. The study found high levels of psychological empowerment and academic self-efficacy among the sample, there were no significant differences in psychological empowerment scores by gender or department. However, important differences based on academic level favored students in field training with a thesis. Similarly, academic self-efficacy scores showed no significant differences by gender or department but favored students at the thesis level. The findings highlighted the predictive role of psychological empowerment in academic self-efficacy among graduate students at the College of Education. and Recommendations: include faculty and academic leaders at the College of Education in supporting psychological empowerment among graduate students and educating them on its importance for enhancing self-confidence and decision-making in academic and practical contexts.